RISK ASSESSMENT IN AUDITING - IRINA Egorova; SVETLANA Erendzhenova (Учёт. Анализ. Аудит)
The article is dedicated to one of the most controversial and debated issues among persons who are engaged in auditing activities at the present stage - the assessment of audit risk while conducting the auditing of financial statements. In the field of auditing, risk can be viewed as the probability of admitting some wrong actions or the appearance of some inaccurate information that could influence the auditor’s opinion. The importance and timeliness of the study of this issue boils down to the fact that the omissions and errors in the financial statements will always be present due to the influence of various external and internal factors both on accounting itself and onthe preparation of financial statements. The auditor, in turn, has to assess the risk of failing to detect these mistakes and to develop certain procedures to reduce this risk to an acceptable low level. The article provides a description of the components of auditing risk, models of risk assessment and models for its calculation, assessment approaches; it also presents different methods of auditing risk assessment.